Crystallization behavior, morphology and crystal transformation of blends of isotactic Poly(1-Butene) with propene-hexene copolymer. (21st November 2019) - Ruiz de Ballesteros, Odda; De Rosa, Claudio; Auriemma, Finizia; Malafronte, Anna; Scoti, Miriam
Abstract: The crystallization behavior and the morphology of blends obtained by mixing a highly crystalline and isotactic poly(1-butene) (iPB) and a copolymer of isotactic polypropylene (iPP) with 26 mol% of 1-hexene (C3C6 copolymer) have been studied. The C3C6 copolymer does not crystallize from the melt but the amorphous sample crystallizes into the trigonal form of iPP by aging at room temperature. All the blends crystallize from the melt in form II of iPB and the aging at room temperature induces transformation into form I and crystallization of the C3C6 copolymer. Both the melt crystallization of form II and its transformation into form I of iPB are retarded in the blends by the presence of the C3C6 component, whereas the crystallization from amorphous phase of the C3C6 copolymer is accelerated thanks to the nucleating effect of the preformed iPB crystals. A good inter-mixing of the two components occurs by solution blending. However, the initial state of the blend obtained by precipitation from solution is not at equilibrium and at 200 °C phase separation takes place by effect of spinodal decomposition, and the degree of demixing increases with increasing the residence time at 200 °C. The final morphology of the iPB/C3C6 blends depends on the composition and can be controlled and modulated by changing time and temperature of melt treatment. Graphical abstract: Image 1 Highlights: The crystallization behavior and morphology of iPB/C3C6 blends are studied. C3C6 copolymer retards the Form II .→ Form I transition of iPB. iPB accelerates crystallization of the C3C6 copolymer by nucleating effect. Blend morphology can be modulated by changing composition and melt treatment.